Self-expandable duodenal metal stent placement for the palliation of gastric outlet obstruction over the past 20 years - Reijm, Agnes N.; Zellenrath, Pauline A.; van der Bogt, Ruben D.; van Driel, Lydi M. J. W.; Siersema, Peter D.; Bruno, Marco J.; Spaander, Manon C. W. (Endoscopy, 2022)
Introduction Duodenal stent placement is a palliative option for management of malignant gastric outlet obstruction (GOO). In the last 20 years, management of gastrointestinal cancers has considerably changed. It is unknown if these changes have affected clinical outcome of duodenal stent placement.Methods Retrospective cohort study conducted in a tertiary referral center. Patients who underwent duodenal stent placement for GOO-symptoms due to a malignant stricture were included. Primary outcome was GOO-symptom free survival. Secondary outcomes included stent-related adverse event rates. Potential explanatory parameters such as period of stent placement (1998–2009 vs 2010–2019), prior treatments, peritoneal deposits, and stricture length were evaluated using multivariable Cox regression analysis.Results A total of 147 patients (62 % male; median age 64 years) were included. After a median of 28 days after stent placement, 82 patients (57 %) had recurrent GOO-symptoms. GOO-symptom free survival was significantly lower in 2010–2019 (P < 0.01). Time period was the only independent predictor for reduced GOO-symptom free survival (HR 1.76, P < 0.01). Stent-related adverse event rates increased over time (1998–2009: 31 % vs 2010–2019: 37 %). Prior treatment with chemotherapy and/or radiotherapy was significantly associated with an increased risk of adverse events (OR 2.53, P = 0.02).Conclusions Clinical outcome of duodenal stent placement did not improve over time. The decreased GOO-symptom free survival and increased adverse event rate in more recent years are probably related to the chemo- and/or radiotherapy treatment provided prior to duodenal stent placement.